Hubungan Antara Identitas Sosial dan Sikap Toleransi Terhadap Keberagaman Sebagai Wujud Kewarganegaraan. - Evania Nathaniela Chrisna Putri (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2025)
This study examines the relationship between social identity and tolerance toward diversity as an expression of citizenship in pluralistic societies. The aim of the research is to analyze how individuals’ identification with social groups relates to inclusive attitudes toward social, cultural, and religious differences. A quantitative approach with a cross-sectional survey design was employed. Data were collected from 25 respondents living in diverse social environments using structured questionnaires measuring social identity and tolerance toward diversity. Descriptive and correlational analyses were used to identify response patterns and relationships between variables. The findings indicate that respondents generally exhibit moderate social identification alongside high levels of tolerance, openness, and respect for diversity. Social identity was not found to hinder tolerance; rather, when non-exclusive, it was associated with inclusive attitudes and rejection of discriminatory tendencies toward minority groups. This study contributes to psychological and citizenship research by highlighting the importance of inclusive social identity in fostering tolerance, social harmony, and responsible citizenship in diverse societies.